Performando para existir: nuances históricas da profissionalização das danças de salão em Goiânia - 1990-2020 - Muniz, Andrea Palmerston (2021)
This study is dedicated to the history of ballroom dancing in the city of Goiânia (Brazil) between 1990 and 2020. Its main objective is to understand the transformations and processes of constitution of a specific work area and sociability through ballroom dance in Goiânia, seeking to understand how the practice of this dance marked profound social and cultural changes in the sensibilities and performances of dancers from Goiás; as well as the role that ballroom dancing and the imaginary of the city of Rio de Janeiro perceived as a synonymous of a place that emits knowledge, obtained among ballroom dancing professionals in the city of Goiânia throughout this time. Here, ballroom dancing had its first contours through etiquette and gained cultural rearrangements with the advent of lambada in the 1990s. This study also concerns how this scenario is redrawn, contributing to the emergence of a ballroom dancing market and its products dedicated to the middle and upper classes, rising the teacher training specialized for this market. The sources used in the research were photographs, journalistic material, official documents about the dance cooperatives and oral interviews. It also used studies in cultural history, dance and anthropology studies, in an interdisciplinary perspective to understand cultural performances.